Absorption of thermal radiation by a water-based spray curtain; Thermal Science and Engineering Progress; Vol. 62 - Antonov D. V. Dmitry Vladimirovich; Fedorenko R. M. Roman Mikhaylovich; Volkov R. S. Roman Sergeevich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen